The Valemee Visual System Helps Reduce Risk for Chronic Illness by Promoting Physical Fitness, Self‐Efficacy and Independence in Adults With Intellectual Disabilities. - Dujmovic‐Bračak, Anthony; Blazek, Alisa D.; Post, Emily M.; Goodway, Jacqueline D.; Swain, Carmen B. (Journal of Applied Research in Intellectual Disabilities, 2025)
Introduction: Sedentary behaviour among individuals with intellectual disabilities, driven by barriers such as limited access to adapted programs and low self‐efficacy, contributes to chronic health conditions. This study evaluates the effectiveness of the Valemee Visual System (VVS), a novel tool offering visual support and structured exercise programming, in improving physical fitness and promoting exercise independence in this population. Methods: A repeated measures design was employed with an 8‐week intervention involving 22 participants aged 22–44 with mild to moderate intellectual disabilities. The program utilised the VVS for total body fitness training. Results: Participants demonstrated significant improvements in grip strength, sit‐to‐stand performance, bench press capacity, 400‐m walk time, and flexibility. Self‐efficacy increased, and reduced reliance on prompts indicated greater exercise independence and autonomy. Conclusions: The VVS shows promise in enhancing physical fitness, accessibility, and adherence in adults with intellectual disabilities, supporting long‐term health and reducing chronic disease risk.